Serum biochemical, fatty acid profiles and histological changes in caprine pregnancy ketosis - Mohd Azmi, Amirul Faiz (2017)
Pregnancy ketosis has been recognized as one of the metabolic diseases that affects goat performance as well as meat and milk products. Indeed, this has resulted in low production and economic losses by the goat farms through culling and mortality. Pregnancy ketosis will further lead in failure to meet the sudden surge of demand for goat milk and meat in Malaysia. Pregnancy ketosis in goat mainly occurs in late stage of pregnancy due to inadequate of energy intake as compared to the demand by fetus development. Indeed, failure to meet this demand will further leads to negative energy balance. The main cause of negative energy balance in pregnancy ketosis is the disturbance of carbohydrate metabolism, characterized by high production of ketone bodies and plasma free fatty acid (FFA), as well as damage to the liver. Thus, this project aimed to assess the serum biochemical, fatty acid profiles and histological changes of liver in pregnancy ketosis of goat. Sixteen pregnant does at third trimester of pregnancy were used and divided into control (n=8) and treatment groups (n=8). The animals in the treatment group were induced with ketosis by restricted the energy intake for up to 50% of the daily requirement. The does in control group were fed on Napier grass and goat concentrate with water ad libitum. The ketosis goats were observed for body condition score, subclinical and clinical signs throughout this study. Blood samples were collected and analyzed for glucose, Beta-hydroxybutyrate (BHBA), FFA, calcium, electrolyte (sodium, potassium, chloride), liver enzyme and hormonal levels (cortisol and insulin). Four pregnant does with severe stages of ketosis and four pregnant does in control group were slaughtered according to the Islamic traditions (Halal Slaughter Method) by severing the jugular veins, carotid arteries, trachea and the esophagus. All the liver sampleswere collected for fatty acid profile and histological study. In addition, blood plasma and liver samples were analyzed for fatty acid composition by using gas chromatography. The type of lesions and histological changes of the liver tissues during pregnancy ketosis also were analyzed under microscopic study. In this study, several clinical signs were observed in pregnancy ketosis goat such as teeth grinding and depressed. The presence of >3+ ketone bodies in urine was also found in pregnancy ketosis goat. In this study, the BHBA, FFA, calcium, amino aspartate transferase (AST), gamma glutamyltransferase (GGT) and cortisol hormone were significantly higher in pregnancy ketosis goats as compared to control group. Meanwhile, the concentration of glucose, sodium, potassium, chloride, and insulin hormones were lower in pregnancy ketosis goats as compared to control. Fatty acid composition in blood plasma of pregnant goat with ketosis showed higher level of palmitic, stearic and oleic acid whereas the palmitic, oleic and linoleic acid levels was found higher in liver. There are three types of lesion were found in the liver of pregnancy ketosis goat such as fatty liver, congestion and thrombosis. Furthermore, histological study on fatty liver revealed a similar incidence and intensity of mild liver steatosis with lower cellular vacuolation in hepatocyte presence in healthy late pregnant does. Almost all pregnant does with ketosis state had large amount of small lipid droplets in every hepatocyte of whole liver acinus, with higher number of cellular vacuolation. These findings indeed associated with high BHBA and FFA and low glucose levels for pregnancy ketosis goats. In conclusion, liver are involved in the histopathogenesis of caprine pregnancy ketosis as well as pregnancy ketosis can affect the serum biochemical, hormonal, as well as fatty acid profiles in goats.